Comparison of In-Hospital Outcomes Between Patients With or Without Acute Kidney Injury Developed After Hospitalization Following Acute Coronary Syndrome - Safi, Md Sajjad; Chowdhury, Msi Tipu; Parvin, Tanjima; Ahmed, Khurshed; Sultana, Md Ashraf Uddin; Banerjee, Sajal Krishna (University Heart Journal, 2020)
Background: Acute Kidney Injury (AKI), a common complication of acute coronary syndromes (ACS), is associated with higher mortality and longer hospital stays. ACS patients with renal impairment during hospitalization are associated with adverse in-hospital outcomes in the form of heart failure, cardiogenic shock, arrhythmia, dialysis requirement and mortality. Objective: To compare the in-hospital adverse outcomesof patients with ACS with or without AKI. Materials and Methods: This prospective comparative study was conducted in the Department of Cardiology, BSMMU, Dhaka, during the period of August 2017 to July 2018. A total of 70 eligible patients were included in this study of which 35 patients were included in group A (ACS with AKI) and 35 patients were included in group B (ACS without AKI). AKI was diagnosed, on the basis of increased serum creatinine level 0.3mg/dL from baseline within 48 hours after hospitalization. They were subjected to electrocardiography, blood test for serum creatinine (on admission, 12 hours, 48 hours and at the time of discharge), lipid profile, 2-D echocardiography along with serum troponin, CK MB and electrolytes. Results: It was observed that mean age was 58.0±8.5 years in group A and 55.6±12.3 years in group B. Heart failure was more common in group A than in Group B (74.3% vs 34.2% p=0.001 respectively) and arrhythmia was more common in group A than in Group B (100% vs 74.2% respectively). 7(20%) patients of group A required dialysis. The mean duration of hospital stay was significantly higher in Group A than in the Group B (9.4±2.3 vs 7.2±0.6; p=0.001) days. Multiple logistic regression analysis revealed that heart failure, cardiogenic shock, duration of hospital stay were found to be the independently significant predictors of outcome of the patients with AKI with odds ratio being 5.53 (p=0.001), 4.353 (p=0.001) and 6.92 (p=0.001) Conclusion: This study shows that, heart failure, cardiogenic shock, arrhythmia, dialysis requirement, were more common in the patients with AKI (group A) than in the patients without AKI (group B). The duration of hospital stays were longer in patients with AKI (group A) than in the patients without AKI (group B). Therefore, an important research target is the identification of high-risk patients with ACS experiencing AKI, thereby appropriate medication and follow-up should be implemented. University Heart Journal Vol. 16, No. 1, Jan 2020; 3-10